Diagrammatized method of permanent magnet working-point in Polarized System - Liu Lingshun; Shi Xianjun; Wangfang Wangfang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Polarized magnetic system  has widely been used in  aeronautical , astronautical , military and civilian domain.  Diagrammatized analysis method has advantages of clear physics concept, direct and compendious. The diagrammatized analysis method for work points of the permanent magnet and air magnetic flux for the typical polarized systems are proposed in this paper, which include type differential and bridge magnetic system. The unite calculating expressions are sum up based on the equivalent magnetic voltage model circuit. The diagrammatized analysis method is benefit for understanding the working principle of polarity magnetic system. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1287